Hypothesis: Folklore perpetuated expression of moon-associated bipolar disorders in anecdotally exaggerated werewolf guise. (January 2019) - Erren, Thomas C.; Lewis, Philip
Abstract: We hypothesize that Moon-associated signals, recently linked to rapid cycling bipolar disorder, may have triggered extremely rare instances of extreme manic and aggressive behaviour that may be compatible with the folklore of the werewolf. Very limited literature on instances of clinical lycanthropy or violent/manic/madness behaviour in association with the Moon may be due to very rare lycanthropic psychosis and not knowing which signal(s) could determine Moon-mood associations. Mechanistically, lunar effects related to bipolar disorder, mood changes, and psychosis could involve either, or a combination, of the following: (i) some as of yet non-measurable signal or undefined geoelectric/geomagnetic receptor or higher sensitivity in some humans, (ii) Moonlight affecting sleep and/or circadian rhythm, (iii) perinatal imprinting of susceptibility, (iv) lunar-periodic growth, and subsequent consumption, of or exposure to psychotropic agents. Importantly, remarkable recent studies (2018) suggest that links between some Moon cycles and bipolar disorder are conceivable. Further observations suggest a role for periodic changes in lunar distances in combination with the Earth and Sun positions. Targeted research could use insight from astrophysicists. If causal links between Moon signals and mood were corroborated, sufferers may benefit from improved disease understanding. Herein, we systematically review the literature and synthesize the evidence for and against the hypothesis. The werewolf myth could become another instance of folklore popularizing biological variation worthy of investigation such as the book characters created by the psychiatrist Hoffmann in 1845 as a Christmas present for his son; namely, 'Struwelpeter' and 'Zappel-Philipp' (shock-headed Peter and fidgety-Philipp): Their conspicuous characteristics have since been linked to genetic uncombable hair syndrome and ADHD, respectively. Overall, rather than dismissing (seemingly) trivial and uncertain concepts as 'just folklore', scientists should grapple with the roots, causes, and significance of traditions and tales, including the werewolf legend.